New species of Myrmosinae (Hymenoptera: Mutillidae) from Southeastern Asia - Williams, Kevin A.; Lelej, Arkady S.; Thaochan, Narit (Zootaxa, 2019)
The subfamily Myrmosinae is generally Holarctic in distribution with five species known from the Oriental Region. Three species, Kudakrumia malaenglek sp. nov., Kudakrumia loaibonho sp. nov., and Krombeinella brothersi sp. nov., were recently discovered from Thailand and Vietnam, representing the new Southeasternmost distribution records for this subfamily. Keys to Old World genera of Myrmosinae and to males of Kudakrumia and Krombeinella are also provided. The genus Krombeinella Pate is newly recorded from the Oriental region.